Menurunnya Kandungan Kolesterol Telur Itik dengan Pemberian Bawang Putih Segar dengan Waktu Analisis yang Berbeda - I Nyoman Jaya; Ni Ketut Dewi Haryani; Budi Indarsih (Jurnal Sain Veteriner, 2019)
The purpose of this research is to know the influence of the giving of fresh garlic against a decrease in cholesterol levels duck eggs with different analysis time. To achieve that goal, then conducted a study using 50 tail as control with local feeding without given garlic and 50 tail given 25 g/head/day of fresh garlic. The data were analyzed using T-Test, the parameters are observed in this research are cholesterol levels, triglyceride egg yolk, the consumption of feed, feed conversion, egg production, egg weight, and mortality. Analysis of cholesterol levels and triglycerides egg yolks are done at the study week I, III, and V with the method extract ether and the procedure CHOD-PAP. The results showed that there is a decrease in cholesterol 152.24 mg per dl (72.19%) and triglycerides of 130.56 mg per dl (23.42%) a very sharp from the first week to the third week. The feed consumption, egg weight, egg production, and feed conversion are not affected by the time of analysis. The results of this study indicate that to get the content of cholesterol and low fat, given fresh garlic for three weeks.  Duck Eggs; Garlic; Cholesterol